Primer of ecological restoration - Holl, Karen Davis (Island Press, 2020)
The pace, intensity, and scale at which humans have altered our planet in recent decades is unprecedented. We have dramatically transformed landscapes and waterways through agriculture, logging, mining, and fire suppression, with drastic impacts on public health and human well-being. What can we do to counteract and even reverse the worst of these effects? Restore damaged ecosystems. The Primer of Ecological Restoration is a succinct introduction to the theory and practice of ecological restoration as a strategy to conserve biodiversity and ecosystems. In twelve brief chapters, the book introduces readers to the basics of restoration project planning, monitoring, and adaptive management. It explains abiotic factors such as landforms, soil, and hydrology that are the building blocks to successfully recovering microorganism, plant, and animal communities. Additional chapters cover topics such as invasive species and legal and financial considerations. Each chapter concludes with recommended reading and reference lists, and the book can be paired with online resources for teaching. Perfect for introductory classes in ecological restoration or for practitioners seeking constructive guidance for real-world projects, Primer of Ecological Restoration offers accessible, practical information on recent trends in the field.